2017
DOI: 10.1007/s40266-017-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of β-Hydroxy-β-Methylbutyrate as a New Strategy for the Management of Sarcopenia and Sarcopenic Obesity

Abstract: Sarcopenia is defined as an age-related loss of skeletal muscle mass and function and is recognized as a major clinical problem for older people. Essential amino acid supplementation, particularly β-hydroxy-β-methylbutyrate (HMB), a metabolite of leucine that is produced in skeletal muscle, has been evaluated in several studies as a nutritional approach to enhancing muscle protein synthesis in healthy or frail elderly subjects. Studies performed in in vitro conditions show that HMB may be effective in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…HMB in combination with resistance exercise resulted in (relative) lower values for whole body fat (29, 34, 46) and in decreased adipose fat mass in older adult men (47). No positive effects of HMB supplementation on abdominal fat mass or fat area in muscle have however been found in other studies (31, 32), indicating the use of HMB to reduce fat mass particularly in the treatment of abdominal obesity is less certain (48).…”
Section: Other New Potential Beneficial Effects Of Hmbmentioning
confidence: 82%
“…HMB in combination with resistance exercise resulted in (relative) lower values for whole body fat (29, 34, 46) and in decreased adipose fat mass in older adult men (47). No positive effects of HMB supplementation on abdominal fat mass or fat area in muscle have however been found in other studies (31, 32), indicating the use of HMB to reduce fat mass particularly in the treatment of abdominal obesity is less certain (48).…”
Section: Other New Potential Beneficial Effects Of Hmbmentioning
confidence: 82%
“…reported that percentage fat mass was significantly reduced by 1.1 ± 0.2% in the HMB supplementation group in 75 adults of both genders . In contrast, Rossi's review conveyed that the role of HMB in sarcopenic obesity management is still controversial . Therefore, HMB should contribute more on muscle improvement, while its effect on fat reduction is not very notable.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that an inadequate intake of calories and/or proteins might result in both the loss of muscle mass and the formation of steatosis. Omega 3 fatty acids or β‐hydroxy‐β‐methylbutyrate supplementation might improve muscle mass and function .…”
Section: Non‐alcoholic Fatty Liver Disease and Sarcopeniamentioning
confidence: 99%